CONTROL OVER THE SECURITY SERVICES AS AN INDICATOR OF THE POLITICAL SYSTEM (Security Dialogues, 2025)
Liberal democracy as a current and dominant political model in the world representsa kind of equilibrium of a multitude of social relations and connections between the peoplewho make up the society. Democracy as a form of political arrangement has freedom andequality in its essence.In order to enable or realize these two main postulates, society createsa system based on norms and institutions, which in turn model the citizenship of man today.Part of the institutions of the system are the security institutions, whose main mission is theguarantor of one of the basic human motives, security. The security services, like no otherinstitution, in the realization of their mission use means and methods whose possible abusedevastates the entire political system and society in general. This is the foundation of theneed for adequate control that will ensure their legal operation. Legality in the operation ofthe security services is imperative because their work methodology encroaches on the mostbasic human rights, they have information whose misuse is a flagrant violation of humanfreedom and rights. A fact that is established in the history of mankind.The world, the region and our country are witnessing the abuse of these institutions, whichcreated great consequences for the future. Macedonia has witnessed several abuses of theseinstitutions since independence until now. The last abuse that was discovered in 2015, withthe illegal wiretapping, is the largest so far in terms of its scope and substance. From it,materials were illegally created for a large part of the political and media public, the businesscommunity, the judiciary, the prosecutor’s office as well as other segments of society. Eventoday, the dilemma about the integrity of the persons and the institutions managed bythem, for which there is material from the illegal wiretapping, is still relevant. It is legitimateto question whether we can call ourselves a free society if a large part of the elite dailyperforms important duties aware that someone owns a part of their privacy. Therefore, it isquite natural that the quality of the control of the security services rises to the rank of anindicator of the degree of democracy in a society. Macedonia has entered the fourth decadeof liberal democratic life, from a legal and normative point of view it is creating a model ofparliamentary and civil control of services, but the practice is disappointing, confronting uswith the fact that the form has no substance, that the declarative differs from the real.
Keywords: controlling, overseeing, political system, security services, democracy